If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + 6b = 18 Solving 3a + 6b = 18 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6b' to each side of the equation. 3a + 6b + -6b = 18 + -6b Combine like terms: 6b + -6b = 0 3a + 0 = 18 + -6b 3a = 18 + -6b Divide each side by '3'. a = 6 + -2b Simplifying a = 6 + -2b
| 3t-2= | | -2x+2-4=-2(-x+4) | | 2(3x-5)=-11 | | -2=-(2n-8) | | (8x^3-8x^2-26x-10)/(2x-5) | | 69-5x=22x+24 | | 14+3y=17 | | 25=z/-3 | | x*10-18=52 | | -5(m-4)=12 | | ln(x-3)=ln(5x)+ln(2) | | a/7+12=9 | | 7-8x=76-29x | | 3a-9whena=5 | | -4x-40-6=-3x+6 | | -512^1/3 | | 3/5+x=2/3 | | 3(x+6)=10 | | 48a-21-8= | | 5z+3=28 | | -7+9y+5n-4y-3n-29= | | -7x+3=-9x+7 | | x-2/13=9/13 | | 14-5(3x-7)=-26 | | (4ba^2)(a^4b^0)= | | 25-12x=13 | | b-11=-8 | | 3x^2-9x-27=0 | | (8x-3)(x+2)=4 | | 8x+2-6x=1+x-8 | | -35/12=20/3x | | 10y-11=-2 |